Charcot–Marie–Tooth disease type 2G redefined by a novel mutation in LRSAM1. Issue 6 (30th September 2016) - Peeters, Kristien; Palaima, Paulius; Pelayo‐Negro, Ana L.; García, Antonio; Gallardo, Elena; García‐Barredo, Rosario; Mateiu, Ligia; Baets, Jonathan; Menten, Björn; De Vriendt, Els; De Jonghe, Peter; Timmerman, Vincent; et al.
Abstract : Objective: To identify the unknown genetic cause in a large pedigree previously classified with a distinct form of axonal Charcot–Marie–Tooth disease type 2G (CMT2G) and to explore its transcriptional consequences. Methods: Clinical reevaluation of the pedigree was performed, followed by linkage analysis with the redefined disease statuses, and whole genome and exome sequencing. The impact of the mutation was investigated by immunoblotting and transcriptome sequencing. Results: Thirteen affected individuals over 3 generations displayed mild and quiescent lower‐limb axonal sensorimotor neuropathy. Magnetic resonance imaging (MRI) of lower‐limb musculature systematically showed fatty atrophy in clinical and subclinical mutation carriers. We redefined the disease‐linked region to chr9q31.3‐q34.2 and subsequently identified a novel missense variant in the E3 ubiquitin‐protein ligase LRSAM1 (p.Cys694Tyr). Unlike previous reports, we demonstrated in patients' lymphoblasts that the mutation does not influence overall protein levels of LRSAM1, nor of its ubiquitylation target TSG101. The mutation is associated with several transcriptional changes, including a significant upregulation of another E3 ubiquitin‐protein ligase, NEDD4L, and of TNFRSF21, a key regulator of axonal degeneration. Interpretation: Our findings demonstrate that the isolated genetic entity CMT2G is caused by a missense mutation in LRSAM1 and should be reclassified as CMT2P. MRI of lower‐limb musculature can be used to detect minimal signs of the disease. Transcriptome analysis of patients' cells highlights novel molecular players associated with LRSAM1 dysfunction, and reveals pathways and therapeutic targets shared with amyotrophic lateral sclerosis and Alzheimer disease. Ann Neurol 2016;80:823–833